2010
DOI: 10.1124/dmd.110.033522
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Phenolic Metabolites of Styrene in Mouse Liver and Lung Microsomal Incubations

Abstract: ABSTRACT:Metabolic activation is considered to be a critical step for styreneinduced pulmonary toxicity. Styrene-7,8-oxide is a primary oxidative metabolite generated by vinyl epoxidation of styrene. In addition, urinary 4-vinylphenol (4-VP), a phenolic metabolite formed by aromatic hydroxylation, has been detected in workers and experimental animals after exposure to styrene. In the present study, new oxidative metabolites of styrene, including 2-vinylphenol (2-VP), 3-vinylphenol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Although M3 was a minor metabolite (<0.5%) in human liver microsomes, it was the main metabolite in human recombinant CYP3A4, due to the over‐expression of CYP3A4 activity and an absence of competing enzymes and reactions in the cDNA‐expressed enzyme. The mechanism of the major metabolite M1 (dihydroxylation) in liver microsomes is proposed as the alkene of the acryloyl group was preferentially metabolized to the epoxide by CYP3A4 and hydrolyzed by epoxide hydrolase …”
Section: Resultsmentioning
confidence: 99%
“…Although M3 was a minor metabolite (<0.5%) in human liver microsomes, it was the main metabolite in human recombinant CYP3A4, due to the over‐expression of CYP3A4 activity and an absence of competing enzymes and reactions in the cDNA‐expressed enzyme. The mechanism of the major metabolite M1 (dihydroxylation) in liver microsomes is proposed as the alkene of the acryloyl group was preferentially metabolized to the epoxide by CYP3A4 and hydrolyzed by epoxide hydrolase …”
Section: Resultsmentioning
confidence: 99%
“…Styrene glycol- d 8 (SG- d 8 ), 2-VP, and 3-VP were synthesized in our lab. 19 An HP 5890 Series II gas chromatograph with a capillary GC column (J&W Scientific BD-5MS, 20 m × 0.18 mm id, film thickness 0.18 µm), an HP 5971A mass-selective detector (MSD), and an HP 7673 autosampler was used to analyze metabolite samples. HP Chemstation B.02.05 software was used for GC/MS control and data collection.…”
Section: Methodsmentioning
confidence: 99%
“…4-VP has been reported more toxic than SO, 21,22 and our earlier study also showed that 4-VP was more toxic than 2-VP and 3-VP in mice. 19 The VPs were further metabolized to the corresponding hydroxystyrene oxides, vinylcatechols, and/or vinylhydroquinone in mouse microsomes, 19 but whether these metabolites cause cytotoxicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme kinetic studies were performed following the protocol established in our lab (Shen et al ., 2010). Briefly, a 0.5 mL solution containing recombinant human CYP2E1 (50 pmol), 5 mM MgCl 2 , and 2 mM NADPH in 50 mM phosphate buffer (pH 7.4) was preincubated in a 37 °C water bath shaker for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was initiated by addition of 5.0 μL of various concentrations of styrene, 4-fluorostyrene, 4-chlorostyrene or 4-bromostyrene (final concentration: 0.1–100 μM). The incubation continued for 20 min and was quenched by addition of the same volume of ethyl acetate, followed by spiking with deuterated styrene glycol (styrene glycol- d 8 , prepared in our lab) as internal standard (Shen et al ., 2010). The resulting mixture was vortexed and the organic phase was collected.…”
Section: Methodsmentioning
confidence: 99%